Analisis Yuridis Pendaftaran Indikasi Geografis Berdasarkan Prinsip Kepastian Hukum - Herlin Noviyanti; Yetniwati Yetniwati (Zaaken: Journal of Civil and Business Law, 2021)
Geographical Indication is a sign indicating the area of ​​origin of an item and/or product which due to geographical environmental factors including natural factors, human factors or a combination of these two factors gives a certain reputation, quality, and characteristics to the goods and/or products produced. Indonesia has a lot of potential Geographical Indications. However, the problem that currently occurs is that of the many potential Geographical Indications owned by Indonesia, only very few Geographical Indications are registered. Based on the problems above, the writing draws two formulations of the problem as follows: First, how is the application of the principle of legal certainty in the regulation of registration of geographical indications? Second, how is the mechanism for registering ghis thesis uses a normative juridical research method with legal issues of legal issues of obscurity of norms. The purpose of this study is to find out and analyze how the registration of geographical indications is in the perspective of the law on trademarks and geographical indicatieographical indications in accordance with the laws and regulations? The writing of tons, as well as to find out and analyze how the registration of geographical indications is . and using a research approach, namely a case approach, a statutory approach and a conceptual approach. The results of the study indicate that the application and registration of Geographical Indications contains certain conditions that must be met. Abstrak Indikasi Geografis adalah suatu tanda yang menunjukkan daerah asal suatu barang dan/atau produk yang karena faktor lingkungan geografis termasuk faktor alam, faktor manusia atau kombinasi dari kedua faktor tersebut memberikan reputasi, kualitas, dan karakteristik tertentu pada barang dan/atau produk yang dihasilkan. Indonesia memiliki banyak sekali potensi Indikasi Geografis. Namun persoalan yang saat ini terjadi, dari sekian banyak potensi Indikasi Geografis yang dimiliki oleh Indonesia hanya sedikit sekali Indikasi Geografis yang terdaftar. berdasarkan permasalahan diatas maka penulisan menarik dua rumusan masalah sebagai berikut, Pertama Bagaimana penerapan prinsip kepastian hukum dalam pengaturan pendaftaran indikasi geografis? Kedua, Bagaimana mekanisme pendaftaran indikasi geografis sesuai dengan peraturan perundang undangan? Penulisan skripsi ini menggunakan metode penelitian yuridis normatif dengan isu hukum isu hukum kekaburan norma, Tujuan dalam penelitian ini adalah untuk mengetahui dan menganalisis bagaimana pengaturan pendaftaran indikasi geografis dalam perspektif undang-undang tentang merk dan indikasi geografis, serta untuk mengetahui dan menganalisis bagaimana pendaftaran indikasi geografis. dan menggunakan pendekatan penelitian yaitu pendekatan kasus, pendekatan perundang-undangan serta pendekatan konseptual. Hasil penelitian menunjukan bahwa mengenai Penerapan dan pendaftaran Indikasi Geografis mengandung syarat tertentu  yang harus dipenuhi.